Recent Health Care Expenditure Trends Among Adult Cancer Survivors in United States, 2009-2016. (May 2020) - Rubens, Muni; Ramamoorthy, Venkataraghavan; Saxena, Anshul; Das, Sankalp; Bhatt, Chintan; Veledar, Emir; McGranaghan, Peter; Sundil, Subrina; Shehadeh, Nancy; Viamonte-Ros, Ana; Linhares, Yuliya; Odia, Yazmin; et al.
Abstract : Objective: The objective of this study was to understand recent trends in direct health care expenditures among cancer survivors using novel cost-estimation methods and a nationally representative database. Materials and Methods: This study was a retrospective analysis of 193, 003 adults, ≥18 years of age, using the Medical Expenditure Panel Survey during the years 2009-2016. Manning and Mullahy two-part model was used to calculate adjusted mean and incremental medical expenditures after adjusting for covariates. Results: The mean direct annual health care expenditure among cancer survivors ($13, 025.0 [$12, 572.0 to $13, 478.0]) was nearly 3 times greater than noncancer participants ($4689.3 [$4589.2 to $4789.3]) and were mainly spent on inpatient services, office-based visits, and prescription medications. Cancer survivors had an additional health care expenditure of $4407.6 ($3877.6, $4937.6) per person per year, compared with noncancer participants after adjusting for covariates ( P <0.001). The total mean annual direct health care expenditure for cancer survivors increased from $12, 960.0 (95% confidence interval: $12, 291.0-$13, 628.0) in 2009-2010 to $13, 807.0 ($12, 828.0 to $14, 787.0) in 2015-2016. Conclusions: Given the higher health care expenditures among cancer survivors and the increasing prevalence of cancers, cost-saving measures should be planned through multidisciplinary initiatives, collaborative research, and importantly, health care planning and policy changes. Our findings could be helpful in streamlining health care resources and interventions, developing national health care coverage policies, and possibly considering radically new insurance strategies for cancer survivors.